2022
DOI: 10.3390/ph15091097
|View full text |Cite
|
Sign up to set email alerts
|

Aspalathus linearis (Rooibos) and Agmatine May Act Synergistically to Beneficially Modulate Intestinal Tight Junction Integrity and Inflammatory Profile

Abstract: In order to promote gastrointestinal health, significant increases in the prevalence of gastrointestinal disorders should be paralleled by similar surges in therapeutics research. Nutraceutical interventions may play a significant role in patient management. The current study aimed to determine the potential of Aspalathus linearis (rooibos) to prevent gastrointestinal dysregulation resulting from high-dose trace-amine (TA) exposure. Considering the substantial female bias in functional gastrointestinal disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…In vervet monkeys, rooibos normalised Firmicutes to Bacteroidetes ratio to rescue high-fat high-sugar diet-induced metabolic dysregulation ( Mangwana, 2020 ), and increased relative abundance of beneficial bacterial species ( Faecalibacterium prausnitzii, Prevotella stercorea and P. copri, Akkermansia muciniphia, Bacteroides intestinalis, Desulfovibrio piger and Bifidobacterium adolescentis ). More recent in vitro studies confirmed increased probiotic microbial growth and favourably modulated secretome trace amine content to promote gut health ( Pretorius et al, 2022 ; Pretorius and Smith, 2022 ). Taken together, changes in the gut microbiome are likely to influence host regulation and homeostasis and as such, the potential benefit conferred by rooibos supplementation necessitates additional robust investigation.…”
Section: Rooibos: Doomed To Fail or On The Road To Success?mentioning
confidence: 95%
See 2 more Smart Citations
“…In vervet monkeys, rooibos normalised Firmicutes to Bacteroidetes ratio to rescue high-fat high-sugar diet-induced metabolic dysregulation ( Mangwana, 2020 ), and increased relative abundance of beneficial bacterial species ( Faecalibacterium prausnitzii, Prevotella stercorea and P. copri, Akkermansia muciniphia, Bacteroides intestinalis, Desulfovibrio piger and Bifidobacterium adolescentis ). More recent in vitro studies confirmed increased probiotic microbial growth and favourably modulated secretome trace amine content to promote gut health ( Pretorius et al, 2022 ; Pretorius and Smith, 2022 ). Taken together, changes in the gut microbiome are likely to influence host regulation and homeostasis and as such, the potential benefit conferred by rooibos supplementation necessitates additional robust investigation.…”
Section: Rooibos: Doomed To Fail or On The Road To Success?mentioning
confidence: 95%
“…In fact, rooibos has such high potency that pro-oxidant outcome have been reported for extracted (i.e., concentrated) rooibos when administered in the absence of disease or conditions of oxidative stress ( Joubert et al, 2005 ). Secondly, rooibos constituents quercetin, aspalathin and catechin inhibit lipid peroxidation ( Snijman et al, 2009 ), a mechanism likely responsible for its reported membrane-protective effects of rooibos ( Ulicna et al, 2019 ; Pretorius and Smith, 2022 ). A multitude of studies in cell-free systems and in cell culture have also demonstrated improved antioxidant enzyme activities (particularly for catalase and superoxide dismutase (SOD)) ( Waisundara and Hoon, 2015 ) and mitochondrial bioenergetics ( Mthembu et al, 2021 ).…”
Section: Rooibos: Doomed To Fail or On The Road To Success?mentioning
confidence: 99%
See 1 more Smart Citation